Challenges and Opportunities for Endovascular Treatment of Hemorrhage in Combat Casualty Care. (December 2021) - Kauvar, David; Cotton, Bryan; Khan, Mansoor; Perreira, Bruno; Brenner, Megan; Ferrada, Paula; Horer, Tal; Kirkpatrick, Andrew; Ordoñez, Carlos; Pirouzram, Artai; Roberts, Derek; Duchesne, Juan
Abstract : Abstract: The care of the hemorrhaging patient continues to evolve. The use of endovascular techniques to treat hemorrhage has increased significantly in civilian trauma care over the past 15 years and is identified as a major national trauma care research priority. Endovascular techniques are being increasingly employed to treat major thoracoabdominal arterial injuries and resuscitative endovascular balloon occlusion of the aorta is being adopted at trauma centers as a supportive adjunct to resuscitation in the exsanguinating patient. Emerging endovascular technology offers the opportunity to provide temporary or permanent control of non-compressible torso hemorrhage, which remains a vexing problem in combat casualty care. Endovascular advances have not been translated to the care of combat casualties to any significant degree, however. This review provides a summary and analysis of the gap between civilian endovascular hemorrhage control and combat casualty care practice to better align future research and development efforts.